"Do human values matter for promoting brands on social media? How social media users' values influence valuable brand‐related activities such as sharing, content creation, and reviews". Issue 1 (30th October 2019) - Nikolinakou, Angeliki; Phua, Joe
Abstract: Companies consider social media‐based consumer engagement behaviors such as sharing, content creation, and reviews for brands as more valuable than "liking" or consuming brand content. Studies show that branded content shared or created by consumers on social media may drive more brand awareness and loyalty than "likes" (Adweek, 2013). Global companies are increasingly focusing their efforts on motivating consumer‐driven content creation (e.g., Coca‐Cola #shareacoke and Apple #ShotoniPhone; Sprout Index, 2018). However, marketing practitioners are only recently beginning to understand social media audiences who engage in such activities (Adweek, 2018). This study posits that human values can be used to identify and segment audiences for social media‐based valuable brand activities. Three online surveys were conducted with Facebook, Twitter, and Instagram users (ages 18–34) on Amazon Mechanical Turk ( N = 491). The relationship between social media users' values and their reported social media activities was examined. Findings indicate that the human values examined (conservation, self‐enhancement, openness to change and self‐transcendence) are significant drivers of valuable brand‐related social media activities. Companies should address conservation‐driven users in order to elicit brand sharing and creation activities. Companies should target conservation‐driven users for sharing promotions, self‐enhancement‐driven users for sharing informational content and writing of product reviews, and openness to change‐driven users for user‐generated content. Bussinesses should further highlight their corporate social responsibility efforts as a negative relationship is found between users' self‐transcendence values and brand activities. Recommendations are provided on how brandscan address users' values in their social media marketing to motivate sharing of branded content and content creation.